Nervous system targets of RNA editing identified by comparative genomics. - Hoopengardner, B.; Bhalla, T.; Staber, C.; Reenan, R. (Science, 2003)
An unknown number of precursor messenger RNAs undergo genetic recoding by modification of adenosine to inosine, a reaction catalyzed by the adenosine deaminases acting on RNA (ADARs). Discovery of these edited transcripts has always been serendipitous. Using comparative genomics, we identified a phylogenetic signature of RNA editing. We report the identification and experimental verification of 16 previously unknown ADAR target genes in the fruit fly Drosophila and one in humans-more than the sum total previously reported. All of these genes are involved in rapid electrical and chemical neurotransmission, and many of the edited sites recode conserved and functionally important amino acids. These results point to a pivotal role for RNA editing in nervous system function.